2023
DOI: 10.1097/rli.0000000000000951
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Diagnosis and Classification of Rotator Cuff Tears on Shoulder MRI

Abstract: Background: Detection of rotator cuff tears, a common cause of shoulder disability, can be time-consuming and subject to reader variability. Deep learning (DL) has the potential to increase radiologist accuracy and consistency. Purpose: The aim of this study was to develop a prototype DL model for detection and classification of rotator cuff tears on shoulder magnetic resonance imaging into no tear, partial-thickness tear, or full-thickness tear. Materials and Methods: This Health Insurance Portability and Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The model achieved excellent diagnostic performance, with high area under the curve (AUC) values for different tear types. Specifically, the AUCs for full-thickness tears of supraspinatus, infraspinatus, and subscapularis (SSC) tendons were 0.98, 0.99, and 0.95, respectively 31 . Separate authors present a computer-aided diagnostic system based on an optimized CNN for diagnosing RCTs using MRI images.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model achieved excellent diagnostic performance, with high area under the curve (AUC) values for different tear types. Specifically, the AUCs for full-thickness tears of supraspinatus, infraspinatus, and subscapularis (SSC) tendons were 0.98, 0.99, and 0.95, respectively 31 . Separate authors present a computer-aided diagnostic system based on an optimized CNN for diagnosing RCTs using MRI images.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the AUCs for full-thickness tears of supraspinatus, infraspinatus, and subscapularis (SSC) tendons were 0.98, 0.99, and 0.95, respectively. 31 Separate authors present a computer-aided diagnostic system based on an optimized CNN for diagnosing RCTs using MRI images. The computeraided diagnostic system used DL techniques to automatically diagnose shoulder injuries, providing a fast and automated approach while reducing medical errors.…”
Section: Diagnostic Usementioning
confidence: 99%
“…However, the performance of the algorithm in predicting retears of the RC tendons was not evaluated. 36 Similar to Wieser et al, 7 a quantitative 3D analysis of the segmented SSP, ISP, and SSC muscles was performed in this study to obtain more reliable FF and muscle volumes. In the current study, the muscle volume of the intact RC repair group did not change significantly between baseline and follow-up, indicating that successful RC repair halted further progression of fatty infiltration and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The application of new machine learning–based analytical models, multifactorial correlations, and classifiers allows the processing of large data sets and testing thousands of features to identify the relevant markers 35 . Lin et al 36 reported a convolutional neural network for RC tear assessment that achieved excellent performance in detecting full thickness RC tears (AUC, 0.95–0.99). The network was trained on a data set of nearly 12,000 noncontrast shoulder MRIs, using the radiological reports as ground truth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation